Whole-genome fingerprint of the DNA methylome during chemically induced differentiation of the human AML cell line HL-60/S4 - Antwi, Enoch; Olins, Ada; Teif, Vladimir; Bieg, Matthias; Bauer, Tobias; Gu, Zuguang; Brors, Benedikt; Eils, Roland; Olins, Donald; Ishaque, Naveed (Biology open, 2020)
Epigenomic regulation plays a vital role in cell differentiation. The leukemic HL-60/S4 [human myeloid leukemic cell line HL-60/S4 (ATCC CRL-3306)] promyelocytic cell can be easily differentiated from its undifferentiated promyelocyte state into neutrophil- and macrophage-like cell states. In this study, we present the underlying genome and epigenome architecture of HL-60/S4 through its differentiation. We performed whole-genome bisulphite sequencing of HL-60/S4 cells and their differentiated counterparts. With the support of karyotyping, we show that HL-60/S4 maintains a stable genome throughout differentiation. Analysis of differential Cytosine-phosphate-Guanine dinucleotide methylation reveals that most methylation changes occur in the macrophage-like state. Differential methylation of promoters was associated with immune-related terms. Key immune genes, CEBPA, GFI1, MAFB and GATA1 showed differential expression and methylation. However, we observed the strongest enrichment of methylation changes in enhancers and CTCF binding sites, implying that methylation plays a major role in large-scale transcriptional reprogramming and chromatin reorganisation during differentiation. Correlation of differential expression and distal methylation with support from chromatin capture experiments allowed us to identify putative proximal and long-range enhancers for a number of immune cell differentiation genes, including CEBPA and CCNF. Integrating expression data, we present a model of HL-60/S4 differentiation in relation to the wider scope of myeloid differentiation.
Gesehen am 28.10.2020